Hypothesis of general problematization of current philosophy in Mexico (Devenires, 2024)
To date, the question “what is philosophy?” remains valid, since it does not have a unique answer. Here, problematizing its concept does not mean observing an abstract and timeless unknown, but rather evaluating the relationship that may exist between the discourses with which it is defined and its factual social presentation (discipline legitimized and supported by the State). Thus, the article presents an investigation to support the following problematic hypothesis of current philosophy in Mexico: if the conceptual state of philosophy appears both undefined and normalized, and if the conception of philosophy has a fundamental character in its concrete social and guild expression, then, the lack of a concept (clear, systematic and common) would be the biggest problem of current philosophy. The objective is to generate a position in the reader about the possibilities of addressing that conception as a collective problem.
Keywords: metaphilosophy; metadiscipline; disciplinary autonomy